2019
DOI: 10.1007/s12325-019-01126-x
|View full text |Cite|
|
Sign up to set email alerts
|

Combining GLP-1 Receptor Agonists and Basal Insulin in Older Adults with Type 2 Diabetes: Focus on Lixisenatide and Insulin Glargine

Abstract: Estimates suggest that there are currently 122.8 million adults 65-99 years of age living with diabetes, of whom 90-95% are diagnosed with type 2 diabetes (T2D). Over the past two decades, a greater understanding of the complex and multifactorial pathogenesis of T2D has resulted in the development and introduction of new-generation classes of glucose-lowering therapies, which are now extensively endorsed by prevailing guidelines and are increasingly being used worldwide. These newer agents may further assist i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Differences in uptake across the blood–brain barrier (or in brain access through subfornical organs) have been postulated as an explanation [ 20 23 ]. Clinical trial data from patients receiving fixed-ratio combination showed a weight change of − 0,3 to − 0,7 kg for iGlarLixi and − 2 to − 2,7 kg for iDegLira [ 12 , 13 , 16 , 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in uptake across the blood–brain barrier (or in brain access through subfornical organs) have been postulated as an explanation [ 20 23 ]. Clinical trial data from patients receiving fixed-ratio combination showed a weight change of − 0,3 to − 0,7 kg for iGlarLixi and − 2 to − 2,7 kg for iDegLira [ 12 , 13 , 16 , 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although its apparently short half-life, it reduces postprandial glucose levels with once daily dosing through the day which is primarily mediated via delayed gastric emptying 31 . According to previous clinical studies, lixisenatide showed significant beneficial effects on postprandial blood glucose levels and HbA1c reduction in various settings, involving when used as monotherapy and add-on to oral antidiabetics and basal insulin 32 . The starting dose of lixisenatide is 10 µg daily for 2 weeks, which on day 15 is titrated to 20 µg daily.…”
Section: Lixisenatidementioning
confidence: 99%
“…37 Therefore, GLP-1 receptor agonists (RAs) have been developed and are shown to be effective in glucose lowering when prescribed to individuals with T2D. 38 The first two combinations of insulin with GLP- Review degludec or glargine with a GLP-1 RA analog (liraglutide or lixisenatide, respectively) in a fixed ratio [19][20][21]39 (Table 1).…”
Section: Combination Insulin Formulationsmentioning
confidence: 99%